2018
DOI: 10.1002/prp2.445
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological profile of the neuropeptide S receptor: Dynamic mass redistribution studies

Abstract: Neuropeptide S (NPS) is the endogenous ligand of the neuropeptide S receptor (NPSR). NPS modulates several biological functions including anxiety, wakefulness, pain, and drug abuse. The aim of this study was the investigation of the pharmacological profile of NPSR using the dynamic mass redistribution (DMR) assay. DMR is a label‐free assay that offers a holistic view of cellular responses after receptor activation. HEK293 cells stably transfected with the murine NPSR (HEK293mNPSR) have been used. To investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Measuring the peak DMR response turned out to provide a much more robust assay window than measuring the final and sustained DMR response ( Figure 2D ). For this reason, subsequent data depicted in this report was generated with the peak DMR responses, as reported in other DMR studies with different GPCRs ( Schrage et al, 2013 ; Malfacini et al, 2018 ; Ruzza et al, 2018 ). Under these conditions, sucralose generated an EC 50 of 163 μM in this assay ( Figure 2E ; Table 1 ) (pEC 50 3.825 ± 0.174) and only the highest concentration of sucralose (≥2 mM) produced a smaller non-specific effect on the parental U2OS cells [typically around 20–40 pm (pm), Figures 2B,E ].…”
Section: Resultsmentioning
confidence: 99%
“…Measuring the peak DMR response turned out to provide a much more robust assay window than measuring the final and sustained DMR response ( Figure 2D ). For this reason, subsequent data depicted in this report was generated with the peak DMR responses, as reported in other DMR studies with different GPCRs ( Schrage et al, 2013 ; Malfacini et al, 2018 ; Ruzza et al, 2018 ). Under these conditions, sucralose generated an EC 50 of 163 μM in this assay ( Figure 2E ; Table 1 ) (pEC 50 3.825 ± 0.174) and only the highest concentration of sucralose (≥2 mM) produced a smaller non-specific effect on the parental U2OS cells [typically around 20–40 pm (pm), Figures 2B,E ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro pharmacological studies, performed on cell lines stably expressing human and murine NPSRs, revealed that NPS acts as an excitatory neurotransmitter, in light of the ability to elevate intracellular-free Ca 2+ and to stimulate cAMP synthesis, at nanomolar concentrations and in a dose-dependent manner, indicating that the NPSR couples to both G q and G s protein, and thus increases cellular excitability [ 15 , 25 , 29 , 30 ]. Additionally, radioligand binding assays demonstrated that the radiolabeled NPS analog ( 125 I-labeled Tyr 10 -NPS) shows a displaceable binding with increasing concentrations of NPS (Kd = 0.3 nm), suggesting that NPS behaves as a typical neurotransmitter, binding and activating its cognate receptor with high potency and specificity [ 15 , 28 ].…”
Section: The Nps Systemmentioning
confidence: 99%
“…( A ) Interference of the G protein modulators FR, CTX, PTX and gallein with histamine receptor mediated signaling. FR (alias UBO − QIC) selectively silences Gα q/11 signaling by blocking the GDP − release at concentrations 0.1 to 1.0 µM [ 18 , 41 , 44 , 45 , 46 , 47 ]. PTX selectively and irreversibly silences Gα i/o at a concentration of 100 ng/mL by ADP − ribosylation at the Gα − subunit [ 20 , 33 , 37 , 40 , 41 , 42 ].…”
Section: Figurementioning
confidence: 99%
“…As ribosylation leads to a maximum activation of the Gα s protein rather than inhibition of the Gα s protein, the results should be interpreted with caution. FR (alias UBO-QIC) selectively silences Gα q/11 signaling by blocking the GDP-release in the Gα subunit [ 18 , 41 , 44 , 45 , 46 , 47 ], which is a mandatory step in G protein activation. The advantage of such studies is that they can be performed with the same cell model under identical experimental conditions, thereby precluding cell bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation